Re-exploring the anaesthetic and recovery room component of the Diploma in Operating Department Assistance curriculum at a private higher education institution in South Africa - van Zyl, Ann Elizabeth (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.